An ultra‐low‐profile 0.85 mm Nano Hydro balloon to treat wire‐crossable balloon‐uncrossable lesions: A useful tool in CTO armamentarium. Issue 6 (7th February 2021) - Adusumalli, Srikanth; Dautov, Rustem
Abstract: Balloon uncrossable lesions are commonly encountered during chronic total occlusion (CTO) percutaneous coronary intervention (PCI). A sequential strategy and planning are required to tackle such lesions. We present a case series of severely calcified, device uncrossable lesions where the traditional strategies failed and an ultra‐low‐profile (0.85 mm) balloon was crucial to successful PCI. To our best knowledge, this is the first case series describing the use of this balloon in real world.